Lietuviškos knygos bruožai: 1795–1864 m. tematikos klausimai - Žukas, Vladas (Knygotyra, 1983)
In the article are given distinguishing features of Lithuanian book since the division of Lithuanian-Polish state (in 1795 year) till prohibition of Lithuanian book, printed in Latin letters (1864). In that period Lithuanian books were published in Russia (Lithuania, Latvia, Petersburg) and in Prussia (for the most part in Eastern Prussia). The subjects of them are investigated not sufficiently: there are not sistematical bibliography and comprehensive investigations in the field of bookscience. The subjects of the book show the cultural level of nation, the character of social interests and social functions of the book. In Lithuania of that period the polemics had been taking place concerning subjects of the books, which were addressed to the people. The group of conservative intelligents proposed to limit subjects of those books and issue only religious ones and books of elementary content. The educationalists made attempts to widen subjects of books: they edited belleslettres, scientific and science-popular literature. The edition of secular literature was hampered by a weak material basis and censorship. On the ground of the fundamental work “The bibliography of Lit. SSR” (v. I, 1969) and having looked through the Lithuanian books, issued in the investigated period, a statistical chronological-thematic table was made. In the table all books were classified according to 15 items. The statistics shows, that in the investigated period 1043 books were issued. 672 (64,5 %) of them were of religious content and only 371 (35,5%) were secular. The most important types of secular literature were those: ABC-books – 102; belles-lettres and folklore – 52; calendars – 48; agriculture – 24; care of public health and antialcoholic light – 23; linguistics – 11. The most of secular literature, especially that, which had been edited in Eastern Prussia, were only small booklets and leaflets. The given table shows full statistical development of Lithuanian book by the thematic principle, however it does not give exact data about real intercourse with books of various content and according to their importance.